Molecularly Conductive Behavior of Blended Polymer Electrolyte-based CMC/PVA - Mohd Ali, Noor Saadiah; Zhang, Dishen; Nagao, Yuki; Samsudin, Ahmad Salihin (Makara Journal of Technology, 2019)
This study investigated the electrical conduction and structural behavior of blended polymer electrolyte (BPE)-based carboxymethyl cellulose (CMC) and polyvinyl alcohol (PVA) in the development of solid-state electrochemical devices. Based on impedance spectroscopy and correlating Fourier transform infrared (FTIR) with thermogravimetric analysis, a framework was proposed to explain the structural enhancement of the BPE system. As revealed by FTIR, the optimum conductivity of CMC/PVA BPEs was 9.21 × 10−6 Scm−1 for 80:20 composition attributed to the intermolecular attraction between the polymers. Thermal stability of the CMC/PVA was influenced by the formation of a hydrogen bond between the hydroxyl (-OH), carboxylate (-COO-), and ether linkage (-COC-) functional groups. The finding provides insights into blended polymer electrolyte-based CMC/PVA, which is beneficial in designing safe, thin, and lightweight energy storage devices.